Knowledge Transfer for Improvement of Local Administrative Organizations Capacities in Flood Hazard Risk Management using Participatory Geographic Information System at Dan Makham Tia, Kanchanaburi - Sriboonruang, Komsan; Jorncharoen, Nirut; Kumkrua, Malinee (Journal of Letters, 2025)
This research aims to (1) create risk and vulnerability maps of flood hazard using participatory geographic information systems in Dan Makham Tia District, Kanchanaburi Province, (2) transfer knowledge on flood hazards risk management based on data from the flood risk and vulnerability maps to local administrative organizations ; and (3) transfer the action plans based on the maps to improve the capacities of local administrative organizations in flood hazard risk management. The sample groups were officers of Charakhe Phuek Subdistrict Administrative Organization, disaster prevention and mitigation volunteers, public health volunteers, rescue workers, and disaster victim households. The research framework included geographic information system, vulnerability analysis, and systematic knowledge transfer. The results show that the flood hazard risk and vulnerability map consists of 3 components in data analysis which are disaster risk, flood vulnerability, and flood adaptability. For knowledge transfer on flood hazard risk management, the participants were most satisfied with the media and technologies in knowledge transfer (average score of 4.91), followed by the instructors, applicability of knowledge, and training content with the scores of 4.90, 4.88, and 4.87 respectively. Three action plans at each stage of disaster management, i.e. pre-disaster, disaster, and post-disaster, were transferred to local administrative organizations to improve their capacities in flood risk management.